Triphenylamine/carbazole-modified ruthenium(ii) Schiff base compounds: synthesis, biological activity and organelle targeting. Issue 25 (18th June 2020) - Chen, Shujiao; Liu, Xicheng; Huang, Jie; Ge, Xingxing; Wang, Qinghui; Yao, Meimei; Shao, Yue; Liu, Tong; Yuan, Xiang-Ai; Tian, Laijin; Liu, Zhe
Abstract : N -phenylcarbazole/triphenylamine modified Schiff base half-sandwich ruthenium(ii ) compounds showed potential anticancer activity against A549 and HeLa cells. Abstract : Four triphenylamine/carbazole-modified half-sandwich ruthenium(ii ) compounds [(η 6 - p -cymene)Ru(N/O^N)Cl] 0/+ with Schiff base chelating ligands (N/O^N) are synthesized and characterized. The introduction of Schiff base units effectively increases the antitumor activity of these compounds (IC50 : 1.70 ± 0.56–17.75 ± 3.10 μM), which, meanwhile, can inhibit the metastasis of tumor cells effectively. These compounds follow an energy-dependent cellular uptake mechanism, mainly accumulate in lysosomes to destroy their integrity, and then eventually promote apoptosis. In addition, these compounds can induce an increase of intracellular reactive oxygen species (ROS) levels and provide an antitumor mechanism of oxidation, which is confirmed by the decrease of mitochondrial membrane potential (MMP) and the catalytic oxidation of the coenzyme nicotinamide-adenine dinucleotide (NADH). All these indicate that these ruthenium(ii ) compounds are expected to be dual-functional antitumor agents: anti-metastasis and lysosomal damage.